2021
DOI: 10.21037/atm-21-829
|View full text |Cite
|
Sign up to set email alerts
|

The removal of foreign body ingestion in the upper gastrointestinal tract: a retrospective study of 1,182 adult cases

Abstract: Background: Foreign body (FB) ingestion in the gastrointestinal tract is a common and urgent problem observed in children and adults. However, there may be difficulty locating FBs and complications associated with their removal. This study aimed to identify risk factors and complications correlated to the presence and removal of FBs.Methods: This 5-year retrospective study enrolled 1,311 patients between June 2014 and April 2019.Demographic and endoscopic data were collected, containing age, gender, types and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
0
15
0
3
Order By: Relevance
“…The majority of ingested FBs pass spontaneously through the gastrointestinal tract, with 10-20% of them requiring endoscopic removal and <1% requiring surgical intervention [12]. Endoscopic management is the first choice in the treatment of EFBs because it is safe, effective, cost-efficient, and avoids the need for surgery [13]. Moreover, a retrospective analysis of 188 inpatient cases with EFBs between 1996-2006 revealed that the majority of cases of FBs were removed via rigid esophagoscopy, with only five cases of FBs removed via surgery [14].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of ingested FBs pass spontaneously through the gastrointestinal tract, with 10-20% of them requiring endoscopic removal and <1% requiring surgical intervention [12]. Endoscopic management is the first choice in the treatment of EFBs because it is safe, effective, cost-efficient, and avoids the need for surgery [13]. Moreover, a retrospective analysis of 188 inpatient cases with EFBs between 1996-2006 revealed that the majority of cases of FBs were removed via rigid esophagoscopy, with only five cases of FBs removed via surgery [14].…”
Section: Discussionmentioning
confidence: 99%
“…2 The oesophagus is the most common site of foreign body impaction typically occurring at one of four classical points of narrowing, the upper oesophageal sphincter, the aortic arch, adjacent to the left Open access main bronchus and the oesophageal hiatus through the diaphragm. 3 The clinical presentation of impacted oesophageal batteries is variable and depends on the impaction site and time since ingestion. Early symptoms include retrosternal discomfort, heartburn, vomiting, dysphagia and odynophagia.…”
Section: Discussionmentioning
confidence: 99%
“… 2 The oesophagus is the most common site of foreign body impaction typically occurring at one of four classical points of narrowing, the upper oesophageal sphincter, the aortic arch, adjacent to the left main bronchus and the oesophageal hiatus through the diaphragm. 3 …”
Section: Discussionmentioning
confidence: 99%
“…The Complication of foreign body ingestion depends on the site and type of foreign body. Moreover, a partial denture with sharp metal hooks, metal springs, and sharp bone pieces are among the most common and hazardous foreign bodies that result in stula formation or esophagus puncture (2).…”
Section: Introductionmentioning
confidence: 99%